The involvement of central nervous system across the phenotypic spectrum of Pompe disease: a systematic review - Torri, Francesca; Buchignani, Bianca; Unluturk, Zeynep; Vadi, Gabriele; Loprieno, Sara; Battini, Roberta; Mancuso, Michelangelo; Siciliano, Gabriele (Neuromuscular disorders : NMD, 2025)
•CNS involvement in Pompe disease is heterogeneous in clinical presentation and radiological features.•Arterial vessels, white and grey matter can be affected.•CNS affection is present both in IOPD and LOPD subjects.•No uniform methodology has been applied to study CNS.•Standardized protocols are needed to characterize CNS involvement and adopt proper care strategies. Pompe disease is an inherited lysosomal disorder which results in glycogen buildup in various organs and tissues. The phenotypic spectrum of this disorder encompasses infantile and late-onset forms, with variable multisystem involvement. Affection of the central nervous system is known to variably present in infantile forms, while the incidence of disease-related alterations in older patients is more debated. PubMed, Web of Science and Scopus databases were searched for papers regarding brain and spinal cord abnormalities at imaging and pathology, neuropsychological assessment and clinical reports in Pompe disease, without chronological restrictions. The database search identified 609 records, then 282 full-text articles were retrieved for detailed examination. Of these records, 81 were selected, which presented heterogeneity in methodology and overall analyzed small cohorts. Our search highlights the current fragmented evidence presented in the field. It would be advisable to perform a routine CNS assessment at least by imaging and neuropsychological evaluation at the time of diagnosis and as part of a regular follow-up, for IOPD but also for LOPD patients, to better characterize the prevalence and clinical significance of CNS abnormalities and provide a tailored follow-up.